The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/adfm.200800061
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Fabrication of Multitiered Three‐Dimensional Nanostructures in Porous Alumina

Abstract: We present the fabrication of multitiered branched porous anodic alumina (PAA) substrates consisting of an array of pores branching into smaller pores in succeeding tiers. The tiered three‐dimensional structure is realized by sequentially stepping down the anodization potential while etching of the barrier layer is performed after each step. We establish the key processing parameters that define the tiered porous structure through systematically designed experiments. The characterization of the branched PAA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…[17] The biofunctionalization of 3D ordered porous nanostructures with high surface areas, large pore volume, and narrow pore-size distribution provides one efficient avenue for meeting these requirements. [18] Herein, a novel biofunctionalized 3D ordered nanoporous SiO 2 film with streptavidin is developed on a glass slide for preparation of high efficient chemiluminescent (CL) immunosensor.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The biofunctionalization of 3D ordered porous nanostructures with high surface areas, large pore volume, and narrow pore-size distribution provides one efficient avenue for meeting these requirements. [18] Herein, a novel biofunctionalized 3D ordered nanoporous SiO 2 film with streptavidin is developed on a glass slide for preparation of high efficient chemiluminescent (CL) immunosensor.…”
Section: Introductionmentioning
confidence: 99%
“…Non-steady-state formation of branched pores by potential reduction was systematically investigated by Ho and coworkers [159]. The authors fabricated three-dimensional (3D) two and three-tiered branched AAOs by stepping down anodizing potential for each anodizing step while thinning of the barrier layer is performed after each step; AAOs with the first tier having an average pore diameter of 285 nm branching into four 125 nm sub-pores in the second-tier and four 55 nm sub-pores in the third tier (Fig.…”
Section: Potential Reductionmentioning
confidence: 99%
“…Alternatively, several studies reported another type of 3D porous alumina films that consisted of two to four segments with stepwise changes in pore diameters. [20][21][22][23] For instance, Krishnan et al reported a PAA film whose pore diameters changed in a stepwise manner from 55 to 85 nm or vice z E-mail: chusongz@iwate-u.ac.jp versa, via two-step anodization in oxalic and phosphoric acid solutions, assisted by an interface lithography process. 20 Ho et al fabricated a multi-tiered branched PAA film consisting of an array of big pores branching into 2-4 smaller pores in succeeding tiers, by sequentially stepping down the anodization potential while etching the barrier layer after each step.…”
mentioning
confidence: 99%
“…20 Ho et al fabricated a multi-tiered branched PAA film consisting of an array of big pores branching into 2-4 smaller pores in succeeding tiers, by sequentially stepping down the anodization potential while etching the barrier layer after each step. 22 Meng et al 24,25 and Zaraska et al 26 attempted to produce hierarchical PAA films with root-like pore channels by reducing the anodizing potential by a factor of 1/ √ n(n = 2, 3) in an oxalic acid solution from 72 V to 50 V 24 or from 60 V to 30 V 26 to increase the pore cell numbers. However, most of the previous works could only fabricate PAA films with decreasing pore size.…”
mentioning
confidence: 99%
See 1 more Smart Citation